Immunological Computation: Theory and Applications - D Dasgupta (CRC Press, 2009)
Discusses different immunological mechanisms and their relation to information processing and problem solving. This work reviews standard procedures, representations and matching rules that are used in immunological computation models. It examines immune models, including those based on danger theory, cytokine network models and MHC-based models.